In Silico Analysis of the Enzymes Involved in Haloarchaeal Denitrification - Eric Bernabeu; Jose María Miralles-Robledillo; Micaela Giani; Elena Valdés; Rosa María Martínez-Espinosa; Carmen Pire (Biomolecules, 2021)
During the last century, anthropogenic activities such as fertilization have led to an increase in pollution in many ecosystems by nitrogen compounds. Consequently, researchers aim to reduce nitrogen pollutants following different strategies. Some haloarchaea, owing to their denitrifier metabolism, have been proposed as good model organisms for the removal of not only nitrate, nitrite, and ammonium, but also (per)chlorates and bromate in brines and saline wastewater. Bacterial denitrification has been extensively described at the physiological, biochemical, and genetic levels. However, their haloarchaea counterparts remain poorly described. In previous work the model structure of nitric oxide reductase was analysed. In this study, a bioinformatic analysis of the sequences and the structural models of the nitrate, nitrite and nitrous oxide reductases has been described for the first time in the haloarchaeon model Haloferax mediterranei. The main residues involved in the catalytic mechanism and in the coordination of the metal centres have been explored to shed light on their structural characterization and classification. These results set the basis for understanding the molecular mechanism for haloarchaeal denitrification, necessary for the use and optimization of these microorganisms in bioremediation of saline environments among other potential applications including bioremediation of industrial waters.